The Calculations Of Sociological Situation From Indonesia Spontaneous Law During The Coronavirus Pandemic - et. al., Suriansyah Murhaini, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study shows the impact of the Large-Scale Social Restrictions in the Context of Accelerating the Handling of Coronavirus Disease 2019 (Covid-19) policy on tourism in Borneo Island. Collective behaviour theory was implemented to evaluate the socio-economic impacts of the community, and the in-depth interviews were aimed at the leader of Indonesia tourist guide association, the leader of the Indonesia association tourism bureau and agents in Central Borneo, the leader of the tourism community and a questionnaire were carried out for local people affected by the closure of tourism destination. The results showed that the policy causes controversial behaviour of social interaction. The tourism community is more concerned with hunger than Covid-19, and their activities turn to collective behaviour. A group of people are fleeing tourism work but arranging themselves to meet their daily needs, thereby encouraging or resisting social change by the government.